Audit committee contribution in CSR disclosure in sharia compliant companies - Nugraheni, Peni; Muhrisa, Rini; Indrasari, Arum; Muhammad, Rifqi (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
The audit committee as part of corporate governance is expected to have a major contribution in disclosing company information. Especially for sharia compliant companies, where CSR shows a company’s contribution to society and disclosure is part of information transparency. This research aimed to identify audit committee contribution by examining the influence of audit committee characteristics and CSR disclosure. Audit committee characteristics consist of size, expertise, and number of meetings to the corporate social responsibility disclosure. The study employed samples of Indonesian shariah compliant companies for the period of 2017-2021 with 250 data. The data was analyzed using panel data regression. The results showed that the audit committee size had a positive influence, while expertise and number of meetings of audit committee did not influence CSR disclosure. The finding of this study suggested that audit committee in sharia compliant companies, as a corporate governance mechanism, should be able to support the role of the board of commissioners to promote aspects of transparency in Islamic business entities through CSR disclosure.